The nature, origin and significance of luminescent layers in the Bazhenov Shale Formation of West Siberia, Russia. (February 2019) - Shaldybin, M.V.; Wilson, M.J.; Wilson, L.; Lopushnyak, Yu.M.; Brydson, R.; Krupskaya, V.V.; Kondrashova(Deeva), E.S.; Glotov, A.V.; Goncharov, I.V.; Samoilenko, V.V.; Arbuzov, S.I.; Bether, O.V.; et al.
Abstract: Argillites that strongly luminesce under UV radiation were detected in the Bazhenov Shale Formation (BSF) of the West Siberian Basin during routine core examination and found to be persistent over a wide lateral area. The mineralogy and fabric of these luminescent layers were characterized by optical and fluorescence microscopy, SEM, TEM, XRD and IR methods. Optical and fluorescence microscopy showed that the luminescent layers were to a large extent derived from volcanic ash falls and could be described as meta-tuffites, although normal detrital sedimentation continued at the same time. The layers have a thickness of several mm to a maximum of 3–4 cm and can be defined as a clay-rich regional horizons extending for over 500 km. XRD showed that two principal clay minerals were predominant, namely a kaolinite group minerals, (kaolinite-rich) and a mixed-layer illite-smectite (I/S) similar to that found in K-bentonite. Total organic matter in the luminescent layers is much lower than that in the enclosing BSF clayey-silty siliceous sediments above and below as shown by pyrolytic analyses. Evidence is presented that the luminescent characteristic of the argillites is related to their clay mineralogy, specifically to their content of kaolin minerals, although a contribution from nitrogenous organic matter cannot be entirely discounted. In some ways the luminescent argillites can be compared with bentonites associated with ash transformations or with tonsteins in coal beds, which are also derived from volcanic ash falls and contain highly crystalline kaolinite. However, tonsteins originate at or near land surface whereas the argillites were apparently formed in the deep ocean. But just as tonsteins can be used for detailed stratigraphic studies and are valuable in the context of coal exploration, so may the luminescent argillites prove to be significant both stratigraphically and in the search for economic hydrocarbon deposits, bearing in mind that their clay mineralogy may be sensitive to temperature and depth of burial and related to their placement in the oil and gas window. Graphical abstract: Highlights: Luminescent layers in the Bazhenov Shale Formation occur over a wide area of the West Siberian Basin. The luminescent layers are clay-rich and originate from alteration of volcanic ash in a deep ocean environment. The mineralogy of the luminescent layers is dominated by kaolinitic minerals and mixed-layer illite-smectite. The luminescent layers are kaolinitic meta-tuffites, similar to tonsteins and K-bentonites. These layers could be possibly used as lithostratigraphic markers.